Impact of a Healthy Nails Program on Nail-Biting in Turkish Schoolchildren: A Controlled Pretest-Posttest Study - ERGÜN, AYŞE; ŞİŞMAN, FATMA NEVİN (SAGE PUBLICATIONS INC, 2013)
This study was conducted to examine the effect of a healthy nails program on nail-biting in Turkish schoolchildren. This quasi-experimental study was of pretest-posttest control group design. A total of 50 students of a primary school formed the intervention group, while 53 students from the same school formed the control group. Data were collected with a demographic form, a nail-biting follow-up form, and photographs of the fingernails. It was found that 68.9% of students were biting seven or more of their nails; 46.6% had damaged nail beds. In the intervention group, the rate of the children who were not biting their nails (baseline = 0%, 4th week = 56.0%, 8th week = 64.0%) increased significantly compared to the control group (baseline = 0%, 4th week = 15.1%, 8th week = 18.9%). Outcomes indicate the efficacy of the healthy nails program in reducing the nail-biting problem in schoolchildren.
Keywords: health education; elementary; program development; evaluation; role promotion/development; HABIT-REVERSAL; BEHAVIOR-MODIFICATION; COMPETING RESPONSE; MILD AVERSION; DISORDERS; ONYCHOPHAGIA; EFFICACY; GIRLS